2016
DOI: 10.1038/srep28753
|View full text |Cite
|
Sign up to set email alerts
|

Holographic microscopy and microfluidics platform for measuring wall stress and 3D flow over surfaces textured by micro-pillars

Abstract: Understanding how fluid flow interacts with micro-textured surfaces is crucial for a broad range of key biological processes and engineering applications including particle dispersion, pathogenic infections, and drag manipulation by surface topology. We use high-speed digital holographic microscopy (DHM) in combination with a correlation based de-noising algorithm to overcome the optical interference generated by surface roughness and to capture a large number of 3D particle trajectories in a microfluidic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Consequently, this microscale surface passively modulates the small scales of the flow in the wall region, which in turn affects the large scales in the outer flow. Given the size of the pillars, this result is surprising, but it is consistent with the findings by Bocanegra Evans et al ( 29 ), who observed the propagation of the pressure perturbation over 35 times the pillar height.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, this microscale surface passively modulates the small scales of the flow in the wall region, which in turn affects the large scales in the outer flow. Given the size of the pillars, this result is surprising, but it is consistent with the findings by Bocanegra Evans et al ( 29 ), who observed the propagation of the pressure perturbation over 35 times the pillar height.…”
Section: Resultssupporting
confidence: 90%
“…The design freedom available with direct write methodologies was also exploited to introduce pillars with specific spatial distribution (Figure 5c) or height (Figure 5d) with the intent to demonstrate the possibility of device manufacturing with custom surface properties, for potential applications in the field of microfluidics. 30 In particular, a uniform array of pillars exhibits a high contact angle with water due to a Cassie−Baxter state (Figure S7). By introducing regions devoid of pillars (Figure 5c) or with variations in pillar height (Figure 5d), the behavior of water droplets can be manipulated (Video S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similarly, in microfluidic devices for cell sorting, the efficiency of cell capture and separation depends on the contact area between the cells and the solid surfaces. One approach for enhancing the contact area is to employ arrays of micro-pillars, as suggested in [13,14], but this can result in a substantial increase in dissipated power [15,16]. A more powerful approach is to use multi-scale structures, illustrated in fig.…”
Section: Introductionmentioning
confidence: 99%